A Phylogenomic Backbone for Gastropod Molluscs. (29th June 2022) - Uribe, Juan E; González, Vanessa L; Irisarri, Iker; Kano, Yasunori; Herbert, David G; Strong, Ellen E; Harasewych, M G
Abstract: Gastropods have survived several mass extinctions during their evolutionary history resulting in extraordinary diversity in morphology, ecology, and developmental modes, which complicate the reconstruction of a robust phylogeny. Currently, gastropods are divided into six subclasses: Caenogastropoda, Heterobranchia, Neomphaliones, Neritimorpha, Patellogastropoda, and Vetigastropoda. Phylogenetic relationships among these taxa historically lack consensus, despite numerous efforts using morphological and molecular information. We generated sequence data for transcriptomes derived from 12 taxa belonging to clades with little or no prior representation in previous studies in order to infer the deeper cladogenetic events within Gastropoda and, for the first time, infer the position of the deep-sea Neomphaliones using a phylogenomic approach. We explored the impact of missing data, homoplasy, and compositional heterogeneity on the inferred phylogenetic hypotheses. We recovered a highly supported backbone for gastropod relationships that is congruent with morphological and mitogenomic evidence, in which Patellogastropoda, true limpets, are the sister lineage to all other gastropods (Orthogastropoda) which are divided into two main clades 1) Vetigastropoda $s.l.$ (including Pleurotomariida $+$ Neomphaliones) and 2) Neritimorpha $+$ (Caenogastropoda $+$ Heterobranchia). As such, our results support the recognition of five subclasses (or infraclasses) in Gastropoda: Patellogastropoda, Vetigastropoda, Neritimorpha, Caenogastropoda, and Heterobranchia. [Compositional heterogeneity; fast-evolving; long-branch attraction; missing data; Mollusca; phylogenetics; systematic error.]